2017
DOI: 10.1161/jaha.116.004913
|View full text |Cite
|
Sign up to set email alerts
|

Unwarranted Variation in the Quality of Care for Patients With Diseases of the Thoracic Aorta

Abstract: BackgroundThoracic aortic disease has a high mortality. We sought to establish the contribution of unwarranted variation in care to regional differences in outcomes observed in patients with thoracic aortic disease in England.Methods and ResultsData from the Hospital Episode Statistics (HES) and the National Adult Cardiac Surgery Audit (NACSA) were extracted. A parallel systematic review/meta‐analysis through December 2015, and structure and process questionnaire of English cardiac surgery units were also acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 70 publications
1
35
0
1
Order By: Relevance
“…Diseases of the thoracic aorta are increasing in prevalence, accounting for 1% to 2% of all deaths in Western countries 1, 2, 3, 4, 5. In the United States, diseases of the aorta account for more than 40 000 deaths per year 1, 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases of the thoracic aorta are increasing in prevalence, accounting for 1% to 2% of all deaths in Western countries 1, 2, 3, 4, 5. In the United States, diseases of the aorta account for more than 40 000 deaths per year 1, 4.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, diseases of the aorta account for more than 40 000 deaths per year 1, 4. Thoracic aortic diseases (TADs) are often silent entities with a mortality of almost 80% when presenting as life‐threatening emergencies 3, 6. Therefore, early diagnosis and treatment are likely to improve long‐term survival.…”
Section: Introductionmentioning
confidence: 99%
“…Two groups of studies reported approaches to determine UCV, with suggestions to address UCV. The first group of 4 studies applied a framework to determine UCV in population or hospital level data . The second group of 14 studies applied statistical models, most commonly regression analyses, to identify variation that was considered to be deviating at a statistically significant level from standard, appropriate or expected levels of variability …”
Section: Resultsmentioning
confidence: 99%
“…The final study utilized the Theoretical Domains Framework, widely used in determining health behaviours, to qualitatively identify factors perceived to influence practice. The Theoretical Domains Framework was used to explore factors thought to influence deviation from evidence‐based recommendations via interviews based on 12 theoretical domains rather than being used as a framework to understand UCV . Findings suggest that deviation from evidence‐based guidelines in the assessment of patients with mild traumatic brain injury was largely driven by beliefs about the impact on patient outcomes of using assessment or clinical‐decision tools, lack of skills and knowledge in the use of the tools, and lack of social norms in the specialty around the use of such tools .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation